(untitled) (Research, Society and Development, 2021)
This article consists of a literature review that addresses the relationship between dentistry and pregnancy, both in physiological aspects - transmissibility of oral microorganisms from the mother to the child - and in psychological aspects - perception of oral health conditions by pregnant women. Pregnancy is a special period in a woman’s life, in which she becomes more receptive to the modification of habits already acquired and the acquisition of new behaviors. In this context, it is extremely important that the professional knows how the pregnant woman perceives her oral condition, as it is from this perception that she will shape her behavior. For health services, it is based on this knowledge that multidisciplinary educational programs can be developed that prioritize dental prenatal care and ensure early education. It is necessary that pregnant women develop a gradual awareness of the importance of maintaining good oral health conditions, which will make it possible to reduce the experience of caries in their children’s teeth.